Whitney can I be me - Laird-Clowes, Nick 1957- (Arsenal Filmverleih GmbH, 2017)
Six-time Grammy winner Whitney Houston was one of the most successful female recording artists of all time. WHITNEY: CAN I BE ME offers a raw and uncensored look at Whitney Houston, exploring the impact her life and death had on the people around her and the world of music
Original: USA, Großbritannien 2016
Bildformat 16:9
Bonusmaterial: Interview mit Nick Broomfield; Trailer; Trailer-Show
Keywords: Houston, Whitney -- 1963-2012; Film; Biografie; DVD-Video